2023
DOI: 10.1002/pon.6082
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of group therapy to reduce mental distress in women with non‐metastatic breast cancer: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Objective: Group treatments have proven to be effective for many mental disorders and showed beneficial effects in patients with medical illness. Aim of this systematic review and meta-analysis is to summarize the efficacy of group therapy for women with non-metastatic breast cancer. Methods:We included studies comparing group therapy for women with nonmetastatic breast cancer to non-active control groups, active control conditions, and individual psychotherapy. The primary outcome was mental distress, seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…As for patients experiencing evident symptoms but who do not meet criteria for a disorder, close monitoring of symptoms is recommended. Additionally, group psychotherapeutic approaches have shown strong evidence in alleviating distress in oncologic patient samples while maintaining cost-effectiveness ( 102 , 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for patients experiencing evident symptoms but who do not meet criteria for a disorder, close monitoring of symptoms is recommended. Additionally, group psychotherapeutic approaches have shown strong evidence in alleviating distress in oncologic patient samples while maintaining cost-effectiveness ( 102 , 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…71,72 During focus group interactions, women’s conversations were consolatory, consultative, and informative, creating learning opportunities. 73,74 Similarity of experiences fostered positive feelings, commitment, encouragement, belongingness, and a sense of social inclusivity and outcomes, which few studies have reported. Therefore, we recommend additional studies of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…This review was registered in the international prospective register of systematic reviews under the Registration Number D42023414815. For the present study, we relied on 13 recently published meta-analyses testing the efficacy of group therapy for common psychiatric disorders to develop our inclusion criteria (Alldredge et al, 2023;Barkowski et al, 2020;Burlingame et al, 2016Burlingame et al, , 2018Burlingame et al, , 2020Janis et al, 2021;Rosendahl et al, 2023). Eligible studies (a) were randomized controlled trials published in 1990 or later, (b) involved the treatment of behavioral concerns, (c) assessed the efficacy of child group treatment, with no participants older than 18, (d) included at least one comparison condition, and (e) were in English.…”
Section: Methodsmentioning
confidence: 99%